COMMUNICATION WITH STUDENTS AND PEDAGOGICAL PSYCHOLOGY IN TUTORING ACTIVITIES - Khaitov Sherzod Komilovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Effective communication and pedagogical psychology play a vital role in tutoring, ensuring that students receive the guidance and support necessary for academic success. This paper explores key aspects of communication, including verbal and non-verbal interactions, active listening, and constructive feedback, which enhance student engagement and comprehension. Additionally, it examines the relevance of pedagogical psychology in tutoring, focusing on learning styles, motivation, and emotional intelligence. By integrating these principles, tutors can foster a productive and inclusive learning environment. The study highlights best practices for effective student-tutor interactions, such as building rapport, encouraging active learning, and leveraging technology. The insights presented emphasize the necessity of a psychologically informed approach to tutoring, ultimately empowering students to become independent and confident learners.